PENGUATAN SOCIAL AWARENESS DAN OPTIMALISASI PENERAPAN PROTOKOL KESEHATAN PADA ERA NEW NORMAL MELALUI “PROGRAM PELITA” - Putri, Noviani Achmad; Hermanto, Fredy; Ginanjar, Asep; Nisa, Aisyah Nur Sayidatun; Syakuro, Afif Abdan; Listiyo, Deny; Fandilah, Alifia Putri Tisa (Universitas Negeri Semarang, 2021)
The Covid-19 pandemic is still around us. The number of positive cases of Covid-19 in Indonesia has not been fully completed. In an effort to prevent the impact of Covid-19 from getting worse, each country has issued various policies in an effort to suppress the spread of the virus. These various policies are preventive measures so that everyone can avoid transmission. Some of these policies include implementing online learning, reducing activities outside the home, limiting the occurrence of crowds, limiting opening hours or closing some crowded places, using masks, and various other rules. But unfortunately so far there are still many people who do not comply with the Health Protocol. One of them is often found in residents of Tambakrejo, Semarang. Many children, adults, the elderly and even the elderly who do not wear masks, crowd and there are no hand washing facilities. In addition, the lack of literacy on Health Protocol education and low Social Awareness can cause the spread of the Corona Virus to spread. Therefore, preventive measures are needed for residents so that the chain of the spread of Covid-19 can be broken. This condition has moved us as a service team to be able to help and lighten their burden. Through this PPM activity, we try to provide several activities that we put into one program, which we call the “PELITA” (Our Environmental Approach) program. This program aims not only to provide knowledge about new adaptation habit policies, not only to provide education related to Health Protocols but further than that, this service activity seeks to strengthen Social Awareness for residents. So, through this service, Social Awareness has become one of our important focuses in order to lead the community, especially the residents of Tambakrejo, to be able to strengthen the social competence of the Tambakrejo residents so that they can work together in dealing with various Threats, Challenges, Obstacles and Disturbances during this pandemic. The results of this activity are Strengthening Social Awareness and Optimizing the Implementation of Health Protocols in the New Normal Era through the